Harmony – The Traditional Chinese Concept or International Competence? - Katarzyna MAZUR-KAJTA; Bogdan RUSZCZAK (Communications of International Proceedings, 2020)
The aim of this article is to discuss contemporary perceptions of international aspects of harmony from the Chinese, Malaysian, Belarusian, Polish and Portuguese perspectives, as well as to define the relationship between pro-harmoniousness and economic sciences. The objective of this study was to answer the following questions: How does the international community perceive the concept of harmony? Is harmony important in interpersonal communication? What values favour harmony and what factors disrupt harmonious relations? What areas of economic sciences are related to harmony? Can pro-harmoniousness be considered an international competence or is it rather a traditional Chinese concept? The results provide the definition of harmony as balance and cooperation, as well as identify pro-harmoniousness as an important element of interpersonal communication among international competencies.
Keywords: Harmony; Sustainability; Competence; International Competence